Farmers’ Perception and Financial Profitability of Mustard Production in Bangladesh - Uddin, M T; Kundu, N D; Tushar, M T I (Bangladesh Journal of Nuclear Agriculture, 2024)
The study was undertaken to assess farmers’ perception and explore the factors affecting farmers’ decision to adopt mustard production along with estimate financial profitability and identify potentials and problems of mustard production. Based on stratified random sampling, 120 farmers were interviewed using a structured questionnaire to collect primary data from different villages of Ullahpara upazila under Sirajganj district of Bangladesh. A combination of descriptive statistics, mathematical and statistical technique was used to analyze the data and to achieve the objectives. The study depicts that the highest number of the respondents (35%) belong to the 31-45 age group. Seventy two percent respondents were small farmers having land less than 1.0 hectare and they allocated 34% of their farm area for mustard production. Financial profitability analysis shows that mustard production was profitable on both variable cost and total cost basis and its benefit cost ratio (BCR) was more than one. In case of farmers perception, it was revealed that short duration crop, consumers’ preferences, product price, extension services and sharing of work among household members were the main driving factors for mustard production. Applying dichotomous logistic regression model, four factors namely, farmers’ age, number of family members, experience and farm size were found as significant determinants of adoption of mustard production. Large domestic market, limited use of high-yielding varieties, growing demand for mustard oil and attack of pests and diseases were found as important strength, weakness, opportunities and threats of mustard production, respectively. Finally, the study recommends that there are ample opportunities to enhance mustard production by ensuring access to quality seeds, adopting new technologies, securing fair prices, providing input subsidies, and improving institutional credit facilities with favorable terms and conditions. Bangladesh J. Nuclear Agric, 38(1): 65-80, 2024